Revolusi Industri 4.0 dan Tantangan Pendidikan Islam: Meneguhkan Peran Guru sebagai Khalifah dalam Membentuk Generasi Berkarakter - Nur Afif; Adlan Nawawi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Fourth Industrial Revolution and advancements in digital technology present both significant challenges and opportunities for Islamic education. This article explores strategies for shaping a character-driven generation in the digital era through a holistic approach that integrates religious education, ethics, and technology. This approach aims to enhance the quality of learning by leveraging technologies such as online learning, interactive Qur'an applications, and social media, while addressing emerging ethical and moral challenges. The role of teachers as models of Islamic character is crucial in integrating religious values with digital practices and teaching digital ethics. Recommendations include enhancing teacher competencies, developing a holistic curriculum, monitoring digital content, as well as developing Islamic digital platforms and involving parents. By implementing these strategies, it is hoped that the younger generation will face the challenges of the digital era with strong character and solid religious values.